A multi-tracer estimation of groundwater recharge in a glaciofluvial aquifer in southeastern Manitoba. - Cherry, Andrea J. (University of Ottawa (Canada), 2000)
The Sandilands glaciofluvial complex is believed to be a region of significant groundwater recharge in southeastern Manitoba. Chlorofluorocarbon (CFC-11, CFC-12, and CFC-113), tritium (3H) and tritium/helium (3H/3He) groundwater age dating methods were used to estimate and characterize groundwater recharge in the surficial aquifer in the Sandilands. The multi-tracer technique was used to provide comparison between groundwater age estimates and to evaluate if subsurface processes affected groundwater ages. Five sites within the Sandilands were instrumented with shallow nests (11--28 m total depth) of three piezometers with vertical spacings of 2--7 meters to determine groundwater age profiles and to estimate vertical groundwater velocities and recharge rates. Groundwater recharge was estimated at different locations in the study area to assess the spatial variability of recharge rates and to identify possible controlling factors. Piezometric and geochemical data (major ions, delta 18O, delta13CDIC) were also collected to aid in the interpretation of groundwater ages. (Abstract shortened by UMI.)
Keywords: Hydrology.